Konsep Wasiat Wajibah dalam Warisan dan Problematikanya - Hakim, Abdul (Prodi Ahwal Al-Syakhsiyyah STAI Imam Syafi'i Cianjur, 2024)
Conflicts among family members over inheritance issues are still common today. Many heirs feel dissatisfied with the share they receive from the testator's estate. To resolve these conflicts, several concepts of inheritance distribution have emerged, one of which is the mandatory testament. This article aims to understand the nature and legality of the application of mandatory testament in inheritance matters. The research in this article is qualitative research with a literature study method and uses a comparative approach. The research data sources include Laws, muktabar fiqh books, and relevant scientific journals. Compulsory probate was first regulated in Egyptian Law in 1946, then followed by other Arab countries. The scholars differed in their opinions on the issue of compulsory probate, some rejecting and some accepting. Scholars who reject the concept of compulsory bequest argue that the verse on the obligation of bequest has been abrogated (mansūkh) by the verse on inheritance. In contrast, scholars who accept the concept of compulsory bequest argue that the verse on inheritance only abrogates the will to parents and all heirs, but it still applies to grandchildren and relatives who do not get inheritance due to obstruction.